Giro estético do direito: o agenciamento das ficções jurídicas na encenação da liberdade artística - Vanessa Sousa Vieira (2022)
Many and diverse are the possible ways of approaching law and art. The first of them, in this work, begins with the aesthetic subversion of some formal and material expectations about what a research in law means. The academy is also disputed through for the occupation of this space with some sense of poetry, as law also integrates the ways of fictionalizing new worlds, in its simultaneous dimensions of actuality, hope and struggle for justice. Therefore, presenting the aesthetic turn as a regime of understanding of a sensible shared formally and materially, I propose a different look at the way in which law is staged, in situations that involve the weaving of the meanings and effects of artistic freedom. By the methodological choice of montage of three emblematic scenes in which I plan the elements that cross the legal meanings of this freedom, I locate, in time and space, one of the probable points in which the authoritarian tendencies experienced in Brazil were consolidated as a government policy prone to the institutional dismantling of the cultural sector. The assemblages of law, in such situations, reveal, at the same time, its paradoxical incidence and insufficiency in the fixation of life, also demonstrating that, from the moment the legal field decodes artistic freedom as a right, also through it – but not only – it is possible to claim the possibility of creating and accessing cultural manifestations. Starting from the negative premises of censorship as an impossibility and hate speech as a limit to artistic freedom in the Democratic State of Law, the opening to the aesthetic turn speaks of a daily experience of the normativities that enter the institutions, but also escape them, in an ethical invitation to understanding that stage games and power struggles are constituents of law, of which we are not only spectators or accomplices, but also agents.